2023
DOI: 10.1111/cea.14277
|View full text |Cite
|
Sign up to set email alerts
|

Epigenome alterations in food allergy: A systematic review of candidate gene and epigenome‐wide association studies

Abstract: Objective:The aim of this study was to systematically review the evidence across studies that assessed DNA methylome variations in association with food allergy (FA).Design: A systematic review of the literature and meta-analysis were carried out within several databases. However, the risk of bias in the included articles was not evaluated.Data sources: PubMed, Cochrane Database of Systematic Reviews, and Web of Science were used to search up to July 2022. Eligibility criteria:We included targeted and epigenom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 57 publications
(230 reference statements)
0
4
0
Order By: Relevance
“…For example, among the existing EWAS of food allergy, 11 genes have epigenetic loci reported in at least two studies, while many more were found in only one study. 26 between epigenetic changes and outcomes that may better inform on potential functional effects of epigenetics. 27 Third, testing of findings in independent cohorts additionally strengthens findings and the likelihood that results are relevant beyond the studied sample.…”
Section: Moving Forwardmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, among the existing EWAS of food allergy, 11 genes have epigenetic loci reported in at least two studies, while many more were found in only one study. 26 between epigenetic changes and outcomes that may better inform on potential functional effects of epigenetics. 27 Third, testing of findings in independent cohorts additionally strengthens findings and the likelihood that results are relevant beyond the studied sample.…”
Section: Moving Forwardmentioning
confidence: 99%
“…A limited number of population‐based epigenomic and epigenetic studies of food allergy have been conducted overall, with some overlap in food allergy‐associated epigenetic loci detected, but also many distinct findings from each study. For example, among the existing EWAS of food allergy, 11 genes have epigenetic loci reported in at least two studies, while many more were found in only one study 26 . Differences in study design, populations of the sampled participants, targeted cell type, and food allergy outcome definitions certainly contribute to the spectrum of findings reported.…”
Section: Moving Forwardmentioning
confidence: 99%
“…A recent systematic review explored the association between epigenetic changes in candidate genes associated with food allergy. 24 The review found evidence of epigenetic alteration in several gene loci involved in the maintenance of Th1/Th2 balance and Treg differentiation. These epigenetic changes may provide mechanistic insights into the pathogenesis of food allergies and may guide the development of novel diagnostic biomarkers.…”
Section: Allergic Sensitisation To Food Proteinsmentioning
confidence: 99%
“…Epigenetic histone modification and DNA methylation are heritable, reversible changes which affect the functionality of genetic information without changing the nucleotide sequence. A recent systematic review explored the association between epigenetic changes in candidate genes associated with food allergy 24. The review found evidence of epigenetic alteration in several gene loci involved in the maintenance of Th1/Th2 balance and Treg differentiation.…”
Section: Introductionmentioning
confidence: 99%
“…Food ingestion facilitates food allergen sampling by CD103+ dendritic cells from the luminal tract, enabling their presentation to the T-cell compartment, inducing forkhead box protein 3-positive T-regulatory cells and supporting a tolerogenic cytokine milieu. 2,3 A wide range of environmental factors may hinder natural tolerance acquisition, including genetic, [4][5][6] epigenetic, 7 microbial, [8][9][10][11] cutaneous [12][13][14] and gastro-intestinal mechanisms. 15 Disruption of tolerance may result in activation of Th2 cells and class-switching from IgA to allergen-specific IgE antibody manufacture both in the gut-associated lymphoid tissue and mucosal compartment and the development of food allergy.…”
Section: Introductionmentioning
confidence: 99%